Efektivitas Pelatihan Manajemen Stres Pada Personel Kepolisian Biro Sumber Daya Manusia - Muh. Rajan Piara; Ahmad Razak; Nurul Magfirah; Nur Syamsi Isdar; Nurul Izzah (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
This research was conducted to determine the effectiveness of stress management training. Data collection was carried out using questions related to the material presented during the training. This research is quasi-experimental in the form of one group pretest, posttest design. The training was carried out for one day with 14 police personnel as research subjects from the HR Bureau of the South Sulawesi Regional Police. Subjects were measured during the pre-test, given material and treatment, then given a post-test and calculated the comparative value. Data analysis in this study used hypothesis testing to calculate the number of comparisons. The results of this study indicate that before being given stress management training the results obtained were 45%. After being given stress management training, a result of 55% was obtained. The data shows that the subject's knowledge of stress management increased by 10%. The conclusion obtained from the results of this study is that this training is effective in providing understanding and stress management skills to police personnel.